Bolsonaro's take on the 'absence of racism' in Brazil. (January 2020) - Alfonso, Daniel Angyalossy
Historically, the myth has grown up of Brazil as a racial democracy, despite its marginalisation of its substantial Black population, and the writing out of the Black presence from the national narrative. This article seeks to analyse the extremist political position of Jair Bolsonaro in relation to the Black population of Brazil, within the context of the historical trajectory of official discourses surrounding the question of race. The current far-right president has made racist statements throughout his political career, during his campaign and as president. These are framed here within a broader perspective, relating their content to other views of the state, its agents and its ideologues concerning the Black presence in Brazil since the nineteenth century, at the time of the Brazilian Empire and the struggles by Black organisations to assert their place in the nation.